2015
DOI: 10.4172/2151-6219.1000182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oil Price and Shocks on Economic Growth of Pakistan: Multivariate Analysis (Sectoral Oil Consumption)

Abstract: Oil is becoming the most prominent indicator of economic growth in Pakistan with increase of its demand. Also oil prices are doing their main contribution to impact the GDP of Pakistan including different shock dummies in data. In this study, Cobb-Douglas production function has used to construct three models by introducing three major sectors of oil consumption of Pakistan (Transport, Power and Industrial sector oil consumption) and Pakistan's oil price variable to investigate the impact on GDP. ADF(1979) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Similarly, Alley et al (2014) utilized GMM model to investigate the effect of oil price shocks on economic activities in Nigeria and concluded that oil price uncertainty reduces the level of economic activity in a small open oil-producing economy like Nigeria. Also, Nazir & Hameed (2015), investigated oil prices and GDP in Pakistan using data covering from 1972 to 2011 and concluded that oil prices affected real GDP negatively in the long run. Kiliçarslan & Dumrul (2017) conducted a similar study in Turkey and deployed SVAR analysis for the period from 2005Q1 to 2017Q2.…”
Section: Article In Press -Corrected Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Alley et al (2014) utilized GMM model to investigate the effect of oil price shocks on economic activities in Nigeria and concluded that oil price uncertainty reduces the level of economic activity in a small open oil-producing economy like Nigeria. Also, Nazir & Hameed (2015), investigated oil prices and GDP in Pakistan using data covering from 1972 to 2011 and concluded that oil prices affected real GDP negatively in the long run. Kiliçarslan & Dumrul (2017) conducted a similar study in Turkey and deployed SVAR analysis for the period from 2005Q1 to 2017Q2.…”
Section: Article In Press -Corrected Proofmentioning
confidence: 99%
“…Despite innovations around the world on alternative sources of energy, crude oil still represents the primary source of power in the world today (Nazir & Hameed, 2015). The role of energy in different sectors of a modern economy cannot be over-emphasized.…”
Section: Introductionmentioning
confidence: 99%
“…Volume 14 Issue 2, 2019 Nazir and Hameed (2015), had examined the effect of oil consumption on Pakistan's GDP by using annual data from 1972 to 2011. they used ADF and Johansen Maximum Likelihood method in the study. According to result the long run and dynamic relationship has not detected for industrial oil consumption and oil price variables for model has no short run impact on GDP.…”
Section: Turkish Studies -Economics Finance Politicsmentioning
confidence: 99%